EFFECT OF BIOSTIMULANT TYPE AND CONCENTRATION ON CIPANAS POTATO (Solanum tuberosum L.) ACCLIMATIZATION - Finola Putri Ramadhani; Susiyanti; Sulastri Isminingsih; Zahratul Millah (UIN Sunan Gunung Djati Bandung, 2026)
Potato plantlets produced through tissue culture require an acclimatization phase before transfer to field conditions. Natural biostimulants are expected to enhance plantlet adaptation and growth during this critical stage. This study evaluated the effects of biostimulant type and concentration on the acclimatization of Cipanas potato (Solanum tuberosum L.) plantlets. The experiment was arranged in a split-plot design with three replications. The main plot factor was biostimulant type, consisting of coconut water and aloe vera extract, while the subplot factor was biostimulant concentration (0%, 5%, 15%, and 25%). The observed variables included plant height increase, leaf number, and root number. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level when significant effects were detected. The results showed that biostimulant type, concentration, and their interaction had no significant effect on plant height increase and leaf number during acclimatization. Plant height increase ranged from 0.69 to 2.16 cm, while leaf number ranged from 1.22 to 1.78 leaves plant⁻¹ at 5 weeks after acclimatization (WAA). Root number was the only parameter significantly affected by biostimulant concentration. The control treatment (0%) and 25% concentration produced the highest root numbers, with mean values of 1.56 and 1.16 roots plant⁻¹, respectively, and did not differ significantly according to DMRT. These findings indicate that acclimatization success was primarily influenced by plantlet adaptation to ex vitro conditions, whereas biostimulant concentration contributed mainly to root development.